Transparent Face of Global Competition: The Raw Material Dilemma in the Glass and Glassware Industry - Bulut, Elif; Yesiltepe, Seda Abacioglu (Emerald Group Publishing Ltd, 2025)
PurposeThe purpose of this study is to evaluate the resource utilization efficiency and export performance of countries in the glass and glassware industry, a sector of increasing importance due to sustainability concerns. By focusing on key raw materials used in glass production, this study aims to provide a comparative analysis of countries during the period 2018-2022, a time marked by significant macroeconomic disruptions such as the trade wars. This study also highlights the importance of efficient resource management in the global glass industry, especially in relation to low-carbon production and international trade.Design/methodology/approachThis study provides an innovative evaluation of export performance and raw material dependency in the glass and glassware industry across countries, using advanced multi-criteria decision-making (MCDM) methods: logarithmic percentage change-driven objective weighting, multiple criteria ranking by alternative trace, ranking the alternatives by perimeter similarity, ranking by alternatives median similarity and ranking the alternatives based on the trace to median index. These methods enable a comprehensive analysis of national data, including raw material availability, export capacity and trade dynamics. By integrating these techniques, this study presents a nuanced assessment of how countries navigate critical raw material dependency while maintaining export competitiveness. This approach yields valuable insights into the strategic positioning of nations within this essential global industry.FindingsThis study highlights the strong performance of T & uuml;rkiye, Poland, India and Spain in the glass industry. T & uuml;rkiye's advantage lies in its abundant raw materials, meeting nearly all domestic demand. Poland benefits from its growing production capacity and local silica sand resources, while India's long history of glass production and proximity to ore-rich regions enhance its competitiveness. Spain's recent improvements are linked to macroeconomic factors. In contrast, countries like China, Germany and Japan show lower rankings due to higher raw material consumption. Despite being major producers, their reliance on intensive raw materials affects their overall performance in the industry.Originality/valueThis study brings a unique perspective to the glass and glassware industry by providing a comprehensive evaluation of countries based on their resource utilization and export performance. Unlike previous research, which primarily focuses on production volumes, this study incorporates both the availability of raw materials and the efficiency of their use, offering a more holistic view of national performance. By using innovative MCDM methods, this research goes beyond traditional metrics. In addition, this study emphasizes the growing significance of macroeconomic factors and raw material proximity, contributing new insights to the strategic positioning of countries within the global glass industry.
Keywords: Glass and Glassware; LOPCOW; MCRAT; RAPS; RAMS and RATMI; C44; F14; L52